Agreement in Left Ventricular Function Measured by Echocardiography and Cardiac Magnetic Resonance in Patients With Chronic Coronary Total Occlusion - Li, Jiahui (Front Cardiovasc Med, 2021)
Aims: To determine the agreement between two-dimensional transthoracic echocardiography (2DTTE) and cardiovascular magnetic resonance (CMR) in left ventricular (LV) function [including end-systolic volume (LVESV), end-diastolic volume (LVEDV), and ejection fraction (LVEF)] in chronic total occlusion (CTO) patients. Methods: Eighty-eight CTO patients were enrolled in this study. All patients underwent 2DTTE and CMR within 1 week. The correlation and agreement of LVEF, LVESV, and LVEDV as measured by 2DTTE and CMR were assessed using Pearson correlation, Kappa analysis, and Bland–Altman method. Results: The mean age of patients enrolled was 57 ± 10 years. There was a strong correlation (r = 0.71, 0.90, and 0.80, respectively, all P < 0.001) and a moderately strong agreement (Kappa = 0.62, P < 0.001) between the two modalities in measurement of LV function. The agreement in patients with EF ≧50% was better than in those with an EF <50%. CTO patients without echocardiographic wall motion abnormality (WMA) had stronger intermodality correlations (r = 0.84, 0.96, and 0.87, respectively) and smaller biases in LV function measurement. Conclusions: The difference in measurement between 2DTTE and CMR should be noticed in CTO patients with EF <50% or abnormal ventricular motion. CMR should be considered in these conditions.